Clinical utility of hepatitis B surface antigen levels during the natural history and treatment of chronic hepatitis B infection - Çelik, Mustafa; Arabul, Mahmut; Çekiç, Cem; Vatansever, Sezgin; İpek, Serkan; Aslan, Fatih; Ünsal, Belkis (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Hepatitis B surface antigen (HBsAg) level quantitation may be helpful for understanding the natural history of the disease and its response to treatment. Aim: To determine the serum HBsAg levels during the different phases of chronic hepatitis B (CHB) infection and HBsAg levels of patients who are on treatment with oral antiviral drugs. Material and methods : Patients were categorized in four groups: 9 patients in the immune clearance (IC) phase, 46 patients in the inactive carrier (INC) phase, 25 patients in the reactivated HBeAg negative disease (END) phase and 60 HBeAg negative patients who were on treatment with oral antiviral drugs. HBsAg levels were compared between all groups. HBsAg and HBV DNA levels were compared in three phases of HBV infection. Patients on treatment were divided into two groups, taking lamivudine (L) and taking tenofovir (T). HBsAg levels were compared between END, L and T groups. Results: The HBsAg levels were different between each phase of CHB (p < 0.0001). HBsAg levels were highest in the IC phase and lowest in the INC phase. The HBsAg/HBV DNA ratio was significantly higher in the INC phase than the END and IC phases (p < 0.0001). HBsAg levels were higher in the END phase than the INC phase (p < 0.0001) and higher than the treatment group (p = 0.007). The HBsAg levels had a good correlation with HBV DNA in the natural course of CHB (r = 0.72, p < 0.0001). HBsAg levels were higher in the END group than the L and T groups (p < 0.05). HBsAg levels were higher in the L than the T group (p < 0.05). Conclusions : This study demonstrates that HBsAg levels vary during the natural history of chronic hepatitis B infection. Also, the monitoring of HBsAg levels may help us to determine the best management strategy and to decide future treatment algorithms.